ครูได้ประโยชน์มากมายจากหนังสือ สอนนอกกรอบ: ยุทธวิธีจับใจศิษย์ - ธรรมาภรณ์ วิรัตน์ (JOURNAL OF SOUTHERN TECHNOLOGY, 2015)
หนังสือสอนนอกกรอบ:ยุทธวิธีจับใจศิษย์ เป็นหนังสือที่มีประโยชน์มากต่อครูทุกคน เป็นประโยชน์ในการนำแนวคิดหลักการสำคัญต่าง ๆ ไปปรับใช้ในการจัดการเรียนการสอนมากมายหลายด้าน เช่น การประยุกต์ใช้จิตวิทยาในการจัดการเรียนการสอน การวางแผนจัดการชั้นเรียน หลักการวิธีคิดในการจัดการเรียนรู้เพื่อให้ผู้เรียนประสบความสำเร็จ หลักการและเทคนิคการเป็นครูดี หนังสือนี้ทำให้มองเห็นภาพรวมที่ชัดเจนของครูดี เป็นแบบอย่างที่เหมาะสมในบทบาทหน้าที่สำคัญของครูในแต่ละขั้นตอน เช่น การเตรียมตัวในด้านต่าง ๆ การทำให้นักเรียนเกิดความไว้วางใจ นอกจากนั้นยังกล่าวถึงหลักคิดในการสอนศิษย์ การวางแผนรับมือกับปัญหาต่าง ๆ การสร้างวินัยในชั้นเรียน การส่งเสริมการอ่าน และการทำแผนการสอนที่เหมาะสม Very Beneficial to Teachers from Teaching Outside the Frames: Student Impression Strategies Teaching Outside the Frames: Student Impression Strategies is considered to be very beneficial to every teacher for applying ideas and major principles of many aspects of learning management such as applying psychology for instruction, planning of classroom management, principles of how to manage successful learning activities, and techniques for being good teachers. Moreover, it shows the whole image of being good teachers and being role model in each step such as preparation and building trust. In addition, principles of teaching, planning for solving problems, developing class room disciplines, promoting reading, and making appropriate lesson plans are also included.